Influence of Wahhabism Principles on Tourism Sector in Saudi Arabia - Telekeyeva, Darina (2025)
This bachelor’s thesis explores Wahhabism principles underlying the state structure of the Kingdom of Saudi Arabia. This work aims to assess how and to what extent Wahhabism principles influence the tourism sector in Saudi Arabia and how these principles have been changed or weakened in recent years. For the most part, the thesis focuses on how these principles affect the attraction of Western tourists. The thesis uses mixed research methods, including a description based on secondary academic and media sources and interpretation of statistical data. The results reflect both the influence of the Wahhabi doctrine on the country’s tourism image and the nature of the changes that have taken place as part of recent reforms.